Eficiência do processo de produção e comercialização de sementes de trigo um estudo de caso - Santos, Mariana Manardo dos (2011)
The correct planning of all steps involved in seed production, particularly post-harvest, is extremely important for maintaining a company in a competitive market. The aim of this study was to evaluate the efficiency of processes related to wheat seed production, from the field to the final commercialization of seeds of a producer with self-certification, from Paraná State, in the period of 2006 - 2010. The study was conducted in a company of São Sebastião da Amoreira, Paraná. The amount of wheat seeds received by the Seed Processing Unit, seeds processed, seeds approved for sale and seeds sold were recorded and analyzed for each cultivar processed by the company. On average, the company discarded 30% of all seeds processed; therefore only 70% of seeds processed were effectively sold as seeds. It is important for the company to do a market survey in order to know the customer demand for each cultivar, before sowing the field, in order to minimize losses due to lack of market demand. The preventive control of diseases in the production field is important to avoid losses due to diseases known to compromise the quality and yield of the seeds.